Severe Hyperkalemia: Electrocardiographic Tips for Early Recognition Based on a Case Report - Jorge Gonzalez-Zuelgaray; Patricio I. Frangi; Damián A. Longo; Luisina B. Tosoni; Adrian Baranchuk (University Library System, University of Pittsburgh, 2024)
Background: Rapid correction of severe hyperkalemia is mandatory to survival due to its induction of fatal cardiac arrhythmias. The electrocardiogram serves as the diagnostic tool that can provide insight into such fatal arrhythmias. We present two relevant alterations seen in an 84-year-old female patient with previous anterior myocardial infarction, angioplasty of the circumflex coronary artery, left ventricular ejection fraction of 35%, hypertension, dyslipidemia, paroxysmal atrial fibrillation, and diabetes. The Case: The patient had 4-days with asthenia, adynamia and dyspnea. Lung auscultation showed bilateral base rales with cardiomegaly and interstitial edema identified on chest x-ray. Lab work revealed severe metabolic acidosis, increased plasma urea, creatinine, and severe hyperkalemia (7.9 mEq/liter) considered secondary to acute renal failure. Treatment was initiated with 0.9% sodium chloride, bicarbonate, ASA diuretics and polarizing solution (insulin), resulting in a reduction of hyperkalemia to 6.1 mEq/liter. The patient suffered a cardiorespiratory arrest with recovery and needed intubation and dopamine for hemodynamic support but died 15 hours after admission. Conclusion: The electrocardiographic findings characteristic of severe hyperkalemia were: (i) regular rhythm (cycle length 920-950 ms) without discernible P-waves, which may have a junctional or ventricular origin and less probably could be a manifestation of sinoventricular conduction (preferential conduction from the sinus node to the AV node through specialized tracts without activation of the atrial cardiomyocytes), and (ii) sine wave morphology (markedly wide QRS, absence of ST-segment and broadly based T-waves). These electrocardiographic features, typical of hyperkalemia exceeding 7.0 mEq/liter, are harbingers of malignant arrhythmias and should prompt immediate therapy.